ATPase reaction cycle of P4‐ATPases affects their transport from the endoplasmic reticulum. Issue 3 (14th October 2019) - Tone, Takuya; Nakayama, Kazuhisa; Takatsu, Hiroyuki; Shin, Hye‐Won
Abstract : P4‐ATPases belonging to the P‐type ATPase superfamily mediate active transport of phospholipids across cellular membranes. Most P4‐ATPases, except ATP9A and ATP9B proteins, form heteromeric complexes with CDC50 proteins, which are required for transport of P4‐ATPases from the endoplasmic reticulum (ER) to their final destinations. P‐type ATPases form autophosphorylated intermediates during the ATPase reaction cycle. However, the association of the catalytic cycle of P4‐ATPases with their transport from the ER and their cellular localization has not been studied. Here, we show that transport of ATP9 and ATP11 proteins as well as that of ATP10A from the ER depends on the ATPase catalytic cycle, suggesting that conformational changes in P4‐ATPases during the catalytic cycle are crucial for their transport from the ER. Abstract :